2014
DOI: 10.1182/blood-2014-04-571125
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B cells are enriched within the IgM memory and transitional subsets in healthy donors but are deficient in chronic GVHD

Abstract: Key Points• Human IgM memory B cells possess immunoregulatory properties analogous to transitional B cells.• IL-10-producing B cells are deficient in cGVHD.A subset of regulatory B cells (Bregs) in mice negatively regulate T-cell immune responses through the secretion of regulatory cytokines such as IL-10 and direct cell-cell contact and have been linked to experimental models of autoimmunity, inflammation, and cancer. However, the regulatory function of Bregs in human disease is much less clear.Here we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
145
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(167 citation statements)
references
References 45 publications
12
145
2
4
Order By: Relevance
“…In line with Khoder et al, 24 we found significantly lower Bregs in BLOOD, 12 MARCH 2015 x VOLUME 125, NUMBER 11…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…In line with Khoder et al, 24 we found significantly lower Bregs in BLOOD, 12 MARCH 2015 x VOLUME 125, NUMBER 11…”
Section: Resultssupporting
confidence: 81%
“…The results in the 11 patients with cGVHD in this same study also suggested that IL-10-producing B cells were less frequent in cGVHD patients than in healthy controls and AHSCT recipients without cGVHD. 24 Although we detected a significant concentration of Bregs in the CD27 1 B-cell compartment, we could not replicate the findings of specific enrichment either in the transitional or in the CD5 1 B-cell compartment as previously described. 55,56 Several factors may explain these discrepancies.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…CD19 ?-CD24 hi CD38 hi cells play a key role in inflammation process and autoimmune diseases; however, the role of CD19 ? CD24 hi CD38 hi cells in the development of human cancer is less studied [28]. In this study, first we focused on breast cancer and examined the percentage of T and B regulatory cells and compared them with healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the quantity and quality impairment of Bregs was also observed in human chronic GVHD. 20,21 However, it remains unclear whether Bregs could alleviate acute GVHD while maintaining graft-versus-leukemia (GVL) effects. Here, we show that the immunosuppressive potential of Bregs can be used to suppress acute GVHD without compromising the effects of GVL activity based on results from a mouse model and a clinical cohort study.…”
Section: Cd19mentioning
confidence: 99%